Efektivitas Ekstrak Daun Belimbing Wuluh (Averrhoa Bilimbi L.) Sebagai Inhibitor Pada Baja St37 Dalam Medium Korosif NaCl 3% - Nia Aprilliani; Ediman Ginting Suka; Suprihatin Suprihatin (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2017)
The effectiveness of starfruitleaves extract as an inhibitor of St37 carbon steel in a corrosive medium of 3% NaCl had been researched. The concentration of starfruit leaves extract inhibitor was used 0%. 3%. 5% and 7% with immersion time of 4 and 8 days. Corrosion rate testing was done by weight loss method. The results of the research at each immersion time, showed that the optimum concentration of leaves starfruit extract to inhibit corrosion is 5% and the longer time immersion resulted in decreasing corrosion rate on St37 carbon steel. The maximum effectiveness of inhibitor occurred at 5% concentration with 8 days immersion time which is 78.57%. Characterization using Scanning Electron Microscopy (SEM) showed that the surface of steel looks smoother with white on sampleSt37-8-5 and St37-4-5 showing that tannin in starfruit leaves extract has been adsorbed on the steel surface while St37 carbon steel on St37-8-0 and St37-4-5 has a black steel surface with holes and cracks. Characterization using Energy Dispersive Spectroscopy (EDS) obtained oxygen element on sample St37-8-0 St37-4-0 greater concentration and Fe element smaller on sample St37-8-5 and St37-4-5.